2009
DOI: 10.1007/s10545-008-0937-3
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine tolerance can already reliably be assessed at the age of 2 years in patients with PKU

Abstract: Pre-treatment Phe is unreliable but Phe tolerance is a reliable predictor of the tolerance at 10 years of age, starting at 2 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…Rey et al (1974) first described the influence of age on excretion of OHPAA in children with PKU and found adult threshold values only after 2 years. Accordingly, metabolic data of PKU children older than 2 years conform with respective findings in juvenile patients (Langenbeck et al 1980(Langenbeck et al , 1992, and phe tolerance at 10 years of age can be predicted reliably from the respective data at 2 years (van Spronsen et al 2009). …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Rey et al (1974) first described the influence of age on excretion of OHPAA in children with PKU and found adult threshold values only after 2 years. Accordingly, metabolic data of PKU children older than 2 years conform with respective findings in juvenile patients (Langenbeck et al 1980(Langenbeck et al , 1992, and phe tolerance at 10 years of age can be predicted reliably from the respective data at 2 years (van Spronsen et al 2009). …”
Section: Discussionsupporting
confidence: 72%
“…After description of the 6ML data (Lutz et al 1990;M€ onch et al 1990;Langenbeck et al 2009) and of preliminary results of 5YL (Schmidt et al 1989), we here present for all 5YL study patients the analytical results of phe disposal in blood and of urinary excretion of acidic phe transamination metabolites. Synopsis of the 5YL blood and urine data suggests maturation of phe transamination and/or renal metabolite transport between 6 months and 5 years as the reason for both the predictability of phe tolerance from 2 years on (van Spronsen et al 2009) and reliable classification of PKU/HPA through age 5 phe tolerance data (G€ uttler and Guldberg 1996).…”
Section: Avmentioning
confidence: 99%
“…Recently it has been shown that Phe tolerance may be predictable already at the age of 2 years, and that Phe tolerance at age 2, 3, and 5 years correlates with that at age 10 years [41]. In contrast, reassessment of Phe tolerance may be necessary in adults [42].…”
Section: Phenylalanine Tolerancementioning
confidence: 99%
“…Long-term BH4 responders and long-term BH4 non-responders were compared according to their maximal Phe plasma concentration and their maximal Phe/tyrosine (Tyr) ratio before start of Phe-restricted diet and on Phe-restricted diet, their Phe tolerance at the age of 3 years [21], their results of neonatal BH4 loading test, and their genotype. These variables were used to compare the predictive value for long-term BH4 responsiveness.…”
Section: Predictive Parametersmentioning
confidence: 99%